2023
DOI: 10.1186/s13244-022-01351-z
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations on segmenting rhabdomyosarcoma with diffusion-weighted imaging—What can we do better?

Abstract: Purpose Diffusion-weighted MRI is a promising technique to monitor response to treatment in pediatric rhabdomyosarcoma. However, its validation in clinical practice remains challenging. This study aims to investigate how the tumor segmentation strategy can affect the apparent diffusion coefficient (ADC) measured in pediatric rhabdomyosarcoma. Materials and methods A literature review was performed in PubMed using search terms relating to MRI and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Furthermore, in international studies, variability on the level of the patient and the MRI, reflected in the heterogeneity of reported scan parameters, has to be taken into consideration [ 57 ]. While this might not influence the reported results, it limits the possibility for statistical analysis in DWI data, given non-comparable ADC maps based on a variety of b -values [ 58 ]. Concerning clinical characteristics of the patients, this study was not designed to report on prenatal imaging or outcome, therefore lacking information on prenatal diagnoses and survival of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in international studies, variability on the level of the patient and the MRI, reflected in the heterogeneity of reported scan parameters, has to be taken into consideration [ 57 ]. While this might not influence the reported results, it limits the possibility for statistical analysis in DWI data, given non-comparable ADC maps based on a variety of b -values [ 58 ]. Concerning clinical characteristics of the patients, this study was not designed to report on prenatal imaging or outcome, therefore lacking information on prenatal diagnoses and survival of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may result in more restricted diffusion of water molecules in both extracellular and intracellular spaces, whereas benign SPL has lower cell density and larger extracellular space, resulting in larger ADC values. Study had shown that the diffusion of water molecules in tumors is mainly affected by tumor cell density and the movement of water molecules in the stroma [15]. The cell density of malignant SPL is higher than that of benign SPL, with an increased number of cells per unit volume and a relatively reduced extracellular space, resulting in more restricted diffusion of water molecules and lower ADC values.…”
Section: Discussionmentioning
confidence: 99%